Reconstruction of past asbestos exposure of dockers in the Port of Livorno - Silvestri, Stefano; Nemo, Alessandro (La Medicina del Lavoro, 2014)
Introduction: In the period 1957/1995 more than 200,000 tons of asbestos arrived at the Port of Livorno. This paper attempts to reconstruct the levels of exposure of the dockers during this period, given the absence of any environmental investigations. Methods: The estimates were calculated using the quantities unloaded annually, the number of dockers, the duration and frequency of the unloading operations, the type of packaging and the background pollution. The Time Weighted Average annual exposure allows calculation of a range of cumulative exposure for each worker with a known period of employment. The working methods were reconstructed interviewing employees and the levels of pollution used in the calculations were partly obtained from published data. Results: Significant doses were accumulated by dockers who worked at the port in the 60’s and 70’s. Non-coincidence of the period with the highest imports with that of highest exposure is worth highlighting. Since 1980 the annual average exposure levels were well below the level required for granting insurance compensation benefits. This suggests caution in the use of lists of beneficiaries for epidemiological purposes since the statistical power would be very low. Conclusions: The strongest point of the research is the estimated annual TWA exposure that, regardless of the accuracy of the data, does however allow an epidemiological analysis of the cohort for subgroups with different exposure. The twenty-three cases of mesothelioma already recorded in this cohort were first employed before 1966. This method can be used to estimate exposure in other ports, where basic information is available.